Znaczenie ubezpieczeń finansowych dla funkcjonowania przedsiębiorstwa - Wierzbicka, Ewa (The Significance of Financial Insurance Products for a Company's Activity, 2008)
Financial insurance consists of: 1/ credit insurance, 21 insurance bonding, 3/ insurance of various financial risks. Due to trade credit insurance firms: 1/ cover the majority of potential financial loss, 21 increase the scale of sale transaction with postponed payment, 3/ increase their competitiveness, 4/ lower the risks associated with sale turnover 5/ manage risk with the insurer's help. Firms that make use of trade credit contracts benefit from additional services provided by the insurer, such as: I/ professional advisory service offered by risk assessment specialists, 21 access to information databases regarding credibility and financial standing of present and potential contractors and clients , 3/ help in credit procedures facilitation and client's financial standing monitoring. Financial insurance: 1/ decreases multidimensional risk associated with sales volume and turnover, 21 substitutes firm's shortage of equity (assets), what is particularly important in the case of SME, 3/ increases firm's creditworthiness, particularly in the case of SME , 4/ enables to increase the scale of firm's activity and to improve firm's competitive position.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 467-473